Tree roots and damages in the Jewish catacombs of Villa Torlonia (Roma) - Caneva, G.; Galotta, G.; Cancellieri, L.; Savo, V. (Journal of Cultural Heritage, 2009)
Damages to hypogeal archaeological monuments, caused by the growth of tree roots, are frequently reported in the city of Rome. Problems of compatibility between trees and underground structures may become complex in the case of historical gardens. The Jewish catacombs of Villa Torlonia show relevant conservation problems, some of them arising from damages due to root growth, and consolidating interventions seem to be urgent. Some species in the gardens, especially Ficus carica L., but also Quercus ilex L. and Pinus pinea L., have developed a strong root system, growing for many meters in lateral distance and for some meters vertically. The plants responsible for the various alterations were identiﬁed by their wood anatomy and a methodology to treat similar problems has been proposed. Data collected aim to avoid errors made in managing the plant cover of an archaeological site.
The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS
Keywords: archaeological site; catacombs; hypogeal conservation; rome; tree roots and buildings; Trees; wood anatomy

Tree roots and damages in the Jewish catacombs of Villa Torlonia (Roma) - Caneva, G; Galotta, G; Cancellieri, L; Savo, V (Journal of Cultural Heritage, 2009)
Damages to hypogeal archaeological monuments, caused by the growth of tree roots, are frequently reported in the city of Rome. Problems of compatibility between trees and underground structures may become complex in the case of historical gardens. The Jewish catacombs of Villa Torlonia show relevant conservation problems, some of them arising from damages due to root growth, and consolidating interventions seem to be urgent. Some species in the gardens, especially Ficus carica L., but also Quercus ilex L. and Pinus pinea L., have developed a strong root system, growing for many meters in lateral distance and for some meters vertically. The plants responsible for the various alterations were identiﬁed by their wood anatomy and a methodology to treat similar problems has been proposed. Data collected aim to avoid errors made in managing the plant cover of an archaeological site.
Keywords: archaeological site; catacombs; hypogeal conservation; rome; tree roots and buildings; Trees; wood anatomy